2021
DOI: 10.3390/jmse9010088
|View full text |Cite
|
Sign up to set email alerts
|

On the Tidal Prism: The Roles of Basin Extension, Bottom Friction and Inlet Cross-Section

Abstract: The prism of the Lignano tidal inlet was approximately constant over the last forty years, although the section width has halved. This has led to questions concerning the factors that most influence the tidal prism, and on the applicability of the well-known A–P relationship. A conceptual scheme of the sea–channel–lagoon system has been used to perform a sensitivity analysis of different parameters that characterize both the basin and the inlet cross-section. A 2D hydrodynamic model has been applied to evaluat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
3

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…In fact, recently, Reef et al (2020), using a numerical approach, have shown that when the characteristic size of the lagoon basin increases, the tidal prism tends to an asymptotic value. Petti et al (2021), again using a numerical approach, found the same behavior, highlighting how the prism tends to an asymptotic value both when the surface of the basin grows and when the cross-sectional area of the inlet increases, in both cases with the same tidal amplitude.…”
Section: Introductionsupporting
confidence: 53%
See 2 more Smart Citations
“…In fact, recently, Reef et al (2020), using a numerical approach, have shown that when the characteristic size of the lagoon basin increases, the tidal prism tends to an asymptotic value. Petti et al (2021), again using a numerical approach, found the same behavior, highlighting how the prism tends to an asymptotic value both when the surface of the basin grows and when the cross-sectional area of the inlet increases, in both cases with the same tidal amplitude.…”
Section: Introductionsupporting
confidence: 53%
“…9). The main features of the computational domain derive from the numerical simulations performed by Petti et al (2021), with the aim of understanding the effects on the tidal prism of some geometric and hydrodynamic characteristics of the tidal inlet, channel, and the lagoon basin.…”
Section: Calibration Of the Coefficient Nmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to implying that inlets with high Qℓ will have smaller values of Across, Equation 22 also implies that inlets with higher frictional dissipation (parameterized by a larger Manning's n) must have a larger cross-sectional area in which to convey the same tidal prism as a lower-friction inlet (cf. Petti et al 2021).…”
Section: Relationship Between Tidal Prism and Sediment Transportmentioning
confidence: 99%
“…Given an inlet with fixed Across, increasing the tidal prism Ω (e.g., by increasing the volume of the inland tidal basin) necessitates an increase in current speeds through the inlet to conserve mass. The relationship between Ω and velocity is asymptotic, with its upper limit constrained by friction (currents cannot become indefinitely fast) and basin length (the tide can only propagate inland by some finite length during a 6 hr rising limb; see Petti et al [2021]), but for reasonably small basins, it is expected that increasing the basin volume with Across constant will generate an increase in velocity.…”
Section: Relationship Between Tidal Prism and Sediment Transportmentioning
confidence: 99%